The Marikina shoe industry heritage as seen in the photographs: from 1965 to 2012 An output of the graduate thesis entitled: tracing Marikina city's cultural heritage through the appraisal and documentation of the Marikina shoe industry photographs - Angeles, Nonet M. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Cultural heritage has existed ever since human societies developed systems of belief and attachments to places and objects that they claimed as their own. It is important to discuss cultural heritage because it strongly influences people's sense of identity, loyalties, and behavior. Memory institutions such as archives, libraries, museums, schools, and historic sites have a responsibility for preserving and interpreting the cultural record; hence, there are practical reasons to study cultural heritage.